Mental health care for medical staff and affiliated healthcare workers during the COVID-19 pandemic - Walton, Matthew; Murray, Esther; Christian, Michael D (European heart journal. Acute cardiovascular care, 2020)
The COVID-19 pandemic is an unprecedented challenge for society. Supporting the mental health of medical staff and affiliated healthcare workers (staff) is a critical part of the public health response. This paper details the effects on staff and addresses some of the organisational, team and individual considerations for supporting staff (pragmatically) during this pandemic. Leaders at all levels of health care organisations will find this a valuable resource.